Therapeutic Potential of the Natural Product Mangiferin in Metabolic Syndrome - Mirza, Raihan H.; Chi, Nan; Chi, Yuling (Journal of Nutritional Therapeutics, 2013)
Natural products have long been and continue to be attractive source of nutritional and pharmacological therapeutics. Interest in natural compounds as potential therapies for metabolic syndrome have recently focused on hydroxylated aromatics, such as resveratrol. Another compound of interest in this regard is mangiferin, the predominant constituent of extracts of the mango plant Mangifera indica. Mangiferin has documented antioxidant, cardioprotective and anti-inflammatory effects. Recently, pilot studies indicate bioactivity of this compound in mediating insulin sensitivity and modulating lipid metabolism. In this review we provide information on what we know about the impact of mangiferin on important biological processes involved in metabolic disorders.